2020
DOI: 10.1038/s41598-020-60806-9
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Closed Loop Enclosed Split Ring Biosensor With High Field Confinement for Aqueous and Blood-Glucose Measurements

Abstract: This paper presents a highly sensitive closed loop enclosed split ring biosensor operating in microwave frequencies for measuring blood glucose levels in the human body. The proposed microwave glucose biosensor, working on the principle of high field confinement and concentrated energy, has been tested using both in-vitro and in-vivo methods. This principle allows the sensor to concentrate energy at the surface which results in improved accuracy of measurements. For in-vitro measurements, the biosensor has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…However, there are certain drawbacks associated with the use of these techniques such as low electric field confinement, Q-factor, and sensitivity, which restrict their use in many applications and limit the range of permittivity detection. To enhance the sensitivity, the electric field must be highly confined on and around the sensor so that most of the energy will be concentrated on desired area [ 117 ]. Table 7 demonstrates the recent designs of microwave resonators aligned with the electric field profile.…”
Section: Discussion and Research Challengesmentioning
confidence: 99%
“…However, there are certain drawbacks associated with the use of these techniques such as low electric field confinement, Q-factor, and sensitivity, which restrict their use in many applications and limit the range of permittivity detection. To enhance the sensitivity, the electric field must be highly confined on and around the sensor so that most of the energy will be concentrated on desired area [ 117 ]. Table 7 demonstrates the recent designs of microwave resonators aligned with the electric field profile.…”
Section: Discussion and Research Challengesmentioning
confidence: 99%
“…In this regard, metamaterial resonators offer higher sensitivity than other microwave sensors and they have been reportedly found to sense small variation in EM (electromagnetic) properties of the sample [12]. As a result, metamaterial-based sensors have been presented for dielectric characterisation of ethanol and methanol [13], assessment of dielectric substrates [14], blood glucose monitoring [15][16][17], measurement of material thickness [18], biomedical applications [19], detection of cancerous cells [20], and the evaluation of oils [21]. Metamaterials (MMs) are artificially engineered structures that exhibit negative permeability and permittivity simultaneously [22].…”
Section: Introductionmentioning
confidence: 99%
“…A substrate-integrated waveguide sensor for characterising chemicals at millimetrewave (mm-W) frequency range was presented in [26]. e researchers have proposed various techniques to increase the sensitivity of these sensors by creating a gap between complementary split-ring resonator (CSRR) [27], employing planar microwave resonators [10], and designing closedloop inside split-ring resonator [17].…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that the obtained results were consistent with the readings of a standard glucometer for blood glucose detection. The design of microwave-based glucose sensors is focused on developing a device with high reliability, small size, low limit of detection (LOD), and fast response [ 27 , 28 , 29 ]. High reliability helps to obtain precise results, and a lower LOD is essential for label-free glucose detection [ 30 ].…”
Section: Introductionmentioning
confidence: 99%